1996
DOI: 10.1002/j.1460-2075.1996.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

The fission yeast Cdc1 protein, a homologue of the small subunit of DNA polymerase delta, binds to Pol3 and Cdc27.

Abstract: cdc1+ is required for cell cycle progression in Schizosaccharomyces pombe. Cells carrying temperature‐sensitive cdc1 mutants undergo cell cycle arrest when shifted to the restrictive temperature, becoming highly elongated. Here we describe the cloning and sequencing of cdc1+, which is shown to encode a 462 residue protein that displays significant sequence similarity to the small subunit of mammalian DNA polymerase delta. cdc1+ interacts genetically with pol3+, which encodes the large subunit of DNA polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
135
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(146 citation statements)
references
References 53 publications
(17 reference statements)
9
135
1
Order By: Relevance
“…Moreover, we have constructed a temperature-sensitive dpb2 mutant and found that these cells arrest in late G1/early S phase upon shift to the restrictive temperature. This phenotype has never been observed for temperature-sensitive mutants of either Pol ␣ or Pol ␦, suggesting that Pol ⑀ and Dpb2 provide a novel function(s) during DNA replication initiation (Hughes et al, 1992;D'Urso et al, 1995;MacNeill et al, 1996;Iino and Yamamoto, 1997;Reynolds et al, 1998;Reynolds and MacNeill, 1999). Consistent with this notion, using a chromatin immunoprecipitation (ChIP) assay, we find that both Dpb2 and Pol ⑀ bind replication origins early in S phase, very near to the time of DNA replication initiation.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, we have constructed a temperature-sensitive dpb2 mutant and found that these cells arrest in late G1/early S phase upon shift to the restrictive temperature. This phenotype has never been observed for temperature-sensitive mutants of either Pol ␣ or Pol ␦, suggesting that Pol ⑀ and Dpb2 provide a novel function(s) during DNA replication initiation (Hughes et al, 1992;D'Urso et al, 1995;MacNeill et al, 1996;Iino and Yamamoto, 1997;Reynolds et al, 1998;Reynolds and MacNeill, 1999). Consistent with this notion, using a chromatin immunoprecipitation (ChIP) assay, we find that both Dpb2 and Pol ⑀ bind replication origins early in S phase, very near to the time of DNA replication initiation.…”
Section: Introductionsupporting
confidence: 79%
“…Furthermore, we demonstrate that like cdc20 mutants (Feng and D'Urso, 2001), a temperature-sensitive mutant of dpb2 arrests with a 1C DNA content after shift to the restrictive temperature, suggesting that Dpb2 is required for the onset of S phase. Although it is currently impossible to rule out that DNA replication initiation occurs in cdc20 or dpb2 mutants, it is interesting that early S phase arrest phenotype has never been reported for mutants defective in other DNA polymerases or their associated subunits, all of which arrest with a near 2C DNA content (Hughes et al, 1992;Waseem et al, 1992;MacNeill et al, 1996;MacNeill and Fantes, 1997).Regardless of whether Pol ⑀ is directly involved in DNA replication initiation, it is clear from our studies that Cdc20 and Dpb2 provide an essential function that does not rely on their ability to synthesize DNA. One possibility is that Pol ⑀ binds replication origins early in S phase and is important for either recruiting or stabilizing the interaction of other replication proteins to DNA.…”
mentioning
confidence: 99%
“…Mis6 and Mis12 code for proteins locating at the centromere (Saitoh et al 1997;Goshima et al 1999), while Mis4 is a sister chromatid cohesion molecule (Furuya et al 1998). Mis1, Mis5 and Mis10 are essential for replication (Takahashi et al 1994;MacNeill et al 1996; our unpublished results). These Mis gene products are probably implicated in maintaining the minichromosome through chromosome replication and separation.…”
Section: Introductionmentioning
confidence: 63%
“…Additionally, HYS2 mutants display supersensitivity to hydroxyurea, increased levels of mitotic chromosome loss, and recombination. More recently, MacNeill et al (23) cloned a Schizosaccharomyces pombe gene, cdc1 ϩ , which displays significant sequence identity (34%) to both the p50 subunit of pol ␦ and to HYS2. A physical interaction of the Cdc1 protein with the yeast pol ␦ protein was demonstrated by in vitro co-immunoprecipitation.…”
Section: Fig 10mentioning
confidence: 99%